Acute Esophageal Necrosis in an Alcoholic after Successful Resuscitation from Cardiac Arrest - Amish Shah; Viveksandeep Thoguluva Chandreskar; Ravi Doobay; Arundeep Kahlon; Ioana Amzuta (Case Reports in Gastrointestinal Medicine)
Introduction. We present a patient who presented to the ICU after successful resuscitation from cardiac arrest who was subsequently diagnosed with AEN. Case Presentation. A 66-year-old female presented after cardiac arrest in which return of spontaneous circulation was achieved within 7 minutes after the initiation of CPR. She was intubated on the scene and found to have coffee ground emesis in her bathroom when found unresponsive. Due to the hemodynamically significant GI bleed, patient was started on IV proton pump inhibitor, octreotide, and levophed. Subsequent endoscopy showed diffuse severe mucosal changes characterized by blackness, erythema, friability, granularity, inflammation, and decreased vascular pattern in the middle third of the esophagus and in the lower third of the esophagus. Discussion. AEN is a rare syndrome with a prevalence ranging from 0.001 to 0.2% of EGD. This patient is especially rare as this patient was female and had AEN in the middle esophagus along with lower esophagus. The pathophysiology in this patient is hypothesized that she had cardiac arrest secondary to acute upper GI hemorrhage. Subsequent low-flow state (cardiac arrest) in addition to being in the setting of severe alcohol abuse led to esophageal necrosis.